2013
DOI: 10.1152/ajpendo.00169.2013
|View full text |Cite
|
Sign up to set email alerts
|

6-Mercaptopurine augments glucose transport activity in skeletal muscle cells in part via a mechanism dependent upon orphan nuclear receptor NR4A3

Abstract: The purine anti-metabolite 6-mercaptopurine (6-MP) is widely used for the treatment of leukemia and inflammatory diseases. The cellular effects of 6-MP on metabolism remain unknown; however, 6-MP was recently found to activate the orphan nuclear receptor NR4A3 in skeletal muscle cell lines. We have reported previously that NR4A3 (also known as NOR-1, MINOR) is a positive regulator of insulin sensitivity in adipocytes. To further explore the role of NR4A3 activation in insulin action, we explored whether 6-MP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Decreased gluconeogenic substrate was described as the main mechanism of hypoglycemia. Liu et al [9] confirmed that 6-MP activates nuclear receptor subfamily 4, group A, member 3, resulting in increased glucose transport and glucose transporter type 4 translocation into the basal muscle cell. This mechanism may increase skeletal muscle glucose uptake, and hypoglycemia may occur regardless of the insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased gluconeogenic substrate was described as the main mechanism of hypoglycemia. Liu et al [9] confirmed that 6-MP activates nuclear receptor subfamily 4, group A, member 3, resulting in increased glucose transport and glucose transporter type 4 translocation into the basal muscle cell. This mechanism may increase skeletal muscle glucose uptake, and hypoglycemia may occur regardless of the insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…Among the set of genes under-expressed in RE animals, it is worthy to highlight the Nuclear Receptor Subfamily 4 Group A Member 3 ( NR4A3 ; FC = 2.44, P -value = 1.03 × 10 − 5 ) and 6-Phosphofructo-2-Kinase/Fructose-2, 6-Biphosphatase 2 ( PFKFB2 ; FC = 2.19, P -value = 2.85 × 10 − 7 ) genes. The NR4A3 gene regulates the translocation of the SLC2A4 glucose transporter (also called GLUT4) to the surface of skeletal muscle cells to increase the uptake of glucose [ 25 ], while PFKFB2 catalyses the synthesis of fructose-2, 6-bisphosphate, a key regulator of glycolysis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…6-MP induces stabilization of HIF-1α in the HepG2 hepatocarcinoma cell line [ 21 ], whereas 6-MP decreases HIF-1α protein expression in our model. Regarding glucose uptake, in the L6 model of rat skeletal muscle, 6-MP increases glucose uptake and Glut4 (SLC2A4, solute carrier family 2, member 4) translocation to the cell surface, a process mediated by NR4A3 [ 42 ]. The fact that T cells do not express Glut4 [ 37 ] may explain why 6-MP does not promote increased glucose uptake in our model.…”
Section: Discussionmentioning
confidence: 99%